Diversity of insect in cocoa field at ladang UiTM Jasin / Nurizzatul Syafiqah Abdul Latiff - Abdul Latiff, Nurizzatul Syafiqah (Faculty of Plantation and Agrotechnology, 2019)
The abundance of insects in cocoa area will give huge impacts to the cocoa production. Record shows that in 2007 the production of cocoa beans is 35,180 tonnes meanwhile in 2011 it decreases into 15,000 tonnes. The abundance of insect diversity either pest or predators can contribute to damage particularly on fruit part which can reduce the quality of fruits. This study was conducted at Ladang Uitm Jasin at Cocoa field area. Ten days of sampling were made from September and completed in November 2018. Yellow pan trap were used in this study because the bright yellow colour can attract various kind of insects. A total of 10 families and 4 orders of insect were recorded leading by Hymenoptera followed by Coleoptera, Orthoptera and Hemiptera. The most dominant insects shown were Hymenoptera (62%) and the least insects order was Hemiptera (6%). By using Shannon Index, Coleoptera has the highest diversity in the Cocoa field with H’ = 0.31. The mean populations of orders during ten days of sampling were recorded and there is no significant difference between population of insect and sampling days because the result indicates that all order which is Hymenoptera, Coleoptera, Orthoptera and Hemiptera did not differ significantly (P> 0.05). Hymenoptera has higher mean in third days of sampling while the other is Coleoptera on fourth day, Orthoptera on second day and Hemiptera on the first day of sampling. This study shows that each group of insect currently has higher population at the early collection period because the weather condition is good for searching food, do pollination activities and breeding. These study shows that the abundance of insect cause various impact to the production of cocoa.